Suppression of the mixed lymphocyte reaction in man by a soluble T-cell factor. Specificity of the factor for both responder and stimulator (The Rockefeller University Press, 1978)
J.H., an HLA-Dw2 homozygous multiparous woman, fails to respond to her husband, W.H. (HLA Dw1,-) in the unidirectional mixed lymphocyte reaction. T cells from J.H. were previously shown to suppress the responses of Dw2-positive cells but not Dw2-negative cells to W.H. We now report that a soluble factor released into the supernate of the mixed lymphocyte reaction by J.H. T cells, mediates this suppression. Like the cell from which it is derived, the factor is highly specific for HLA Dw2 in the responder cell and partially specific for the stimulatory alloantigen.